2012
DOI: 10.1021/jp301456j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling to Provide Insight into the Substrate Binding and Catalytic Mechanism of Human Biliverdin-IXα Reductase

Abstract: Human biliverdin-IXα reductase (hBVR-A) catalyzes the conversion of biliverdin-IXα to bilirubin-IXα in the last step of heme degradation and is a key enzyme in regulating a wide range of cellular responses. Though the X-ray structure of hBVR-A is available including cofactor, a crystal structure with a bound substrate would be even more useful as a starting point for protein-structure based inhibitor design, but none has been reported. The present study employed induced fit docking (IFD) to study the substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 55 publications
(111 reference statements)
1
20
0
Order By: Relevance
“…Along with the site‐directed mutagenesis of key catalytic residues, we can now propose a plausible mechanism for this enzyme. Previous analysis of human BVR‐A and BVR‐B suggests that, in these enzymes, biliverdin reduction involves the use of NADPH as a cofactor and proceeds in two steps: (i) proton donation by a hydroxonium ion to a pyrrole nitrogen atom adjacent to C10 of biliverdin to make a cationic intermediate, followed by (ii) hydride transfer from NADPH to C10 to form bilirubin . Based on our results, we also propose that a similar two‐step mechanism is plausible with F 420 H 2 as the hydride donor (Fig.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Along with the site‐directed mutagenesis of key catalytic residues, we can now propose a plausible mechanism for this enzyme. Previous analysis of human BVR‐A and BVR‐B suggests that, in these enzymes, biliverdin reduction involves the use of NADPH as a cofactor and proceeds in two steps: (i) proton donation by a hydroxonium ion to a pyrrole nitrogen atom adjacent to C10 of biliverdin to make a cationic intermediate, followed by (ii) hydride transfer from NADPH to C10 to form bilirubin . Based on our results, we also propose that a similar two‐step mechanism is plausible with F 420 H 2 as the hydride donor (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…None of these mutations led to complete loss of activity, suggesting that the protein is unlikely to be the proton donor in the reaction. Computational analysis of biliverdin reduction by the human BVRs has suggested that the primary proton donor is likely to be a hydroxonium ion, generated via hydrogen bonding of a water molecule with a basic residue such as histidine or arginine . Therefore, using MD simulations we investigated the permeability of solvent within the active site and the hydrogen bonding behavior near the pyrrole nitrogens of interest, N22 on ring B and N23 on ring C [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent stud- ies have reported that BVD has antioxidant abilities through its production of bilirubin, a potent physiological antioxidant. As little as 10 nM bilirubin can protect cells against almost 10,000-fold higher concentrations of H 2 O 2 [14]. The strong antioxidant properties of BVD have been shown in other experimental models, including inflammation, ischemia-reperfusion injury and transplantation [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 89%
“…The structure of BVRA can be divided into two major regions, the catalytic and the regulatory/DNA interaction domains. The N-terminus of BVRB and BVRA contains the catalytic domain and houses a binding motif for NADP(H) and NAD(H) cofactors (10). The C-terminus of BVRA encompasses the domain structures for the basic-leucine-zipper (bZiP) to function as a transcription factor, as well as the nuclear location sequence (NLS) and nuclear export sequences (NES) that are required for translocation into the nucleus and binding to regulatory regions of DNA (11, 12).…”
Section: Bvr Isozymes; the Basicsmentioning
confidence: 99%